The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biom11040500
|View full text |Cite
|
Sign up to set email alerts
|

The Budapest Amyloid Predictor and Its Applications

Abstract: The amyloid state of proteins is widely studied with relevance to neurology, biochemistry, and biotechnology. In contrast with nearly amorphous aggregation, the amyloid state has a well-defined structure, consisting of parallel and antiparallel β-sheets in a periodically repeated formation. The understanding of the amyloid state is growing with the development of novel molecular imaging tools, like cryogenic electron microscopy. Sequence-based amyloid predictors were developed, mainly using artificial neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 25 publications
(28 reference statements)
0
32
0
Order By: Relevance
“…As a starting point to uncover possible physical explanations for the dependence on even/odd spacing, we analyzed representative sequences -- 60:Q 3 N, 60:Q 4 N, 60:Q 5 N, 60:Q, 60:N -- with state-of-the-art amyloid predictors (Charoenkwan et al, 2021; Keresztes et al, 2021; Prabakaran et al, 2021). Using their respective default parameters, we found that most predictors failed entirely to detect amyloid propensity among these sequences.…”
Section: Resultsmentioning
confidence: 99%
“…As a starting point to uncover possible physical explanations for the dependence on even/odd spacing, we analyzed representative sequences -- 60:Q 3 N, 60:Q 4 N, 60:Q 5 N, 60:Q, 60:N -- with state-of-the-art amyloid predictors (Charoenkwan et al, 2021; Keresztes et al, 2021; Prabakaran et al, 2021). Using their respective default parameters, we found that most predictors failed entirely to detect amyloid propensity among these sequences.…”
Section: Resultsmentioning
confidence: 99%
“…We have introduced the Budapest Amyloid Predictor webserver in the work [14] by applying linear Support Vector Machines as the underlying prediction tool [15], and the Waltz dataset [16,17] for training and testing purposes. The Waltz dataset consists of 1415 hexapeptides, from which 514 peptides are experimentally labeled as "amyloidogenic" and 901 hexapeptides as "nonamyloidogenic".…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a hexapeptide was represented by a length 6 × 553 = 3318 vector z. We note that this highly redundant representation has given somewhat better predictions than more concise ones [14] and has not caused any difficulties in what follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations